Potential benefits of medium chain fatty acids in aging and neurodegenerative disease - Dunn, Ella; Zhang, Biqin; Sahota, Virender K.; Augustin, Hrvoje (Frontiers in Aging Neuroscience, 2023)
Neurodegenerative diseases are a large class of neurological disorders characterized by progressive dysfunction and death of neurones. Examples include Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, and amyotrophic lateral sclerosis. Aging is the primary risk factor for neurodegeneration; individuals over 65 are more likely to suffer from a neurodegenerative disease, with prevalence increasing with age. As the population ages, the social and economic burden caused by these diseases will increase. Therefore, new therapies that address both aging and neurodegeneration are imperative. Ketogenic diets (KDs) are low carbohydrate, high-fat diets developed initially as an alternative treatment for epilepsy. The classic ketogenic diet provides energy via long-chain fatty acids (LCFAs); naturally occurring medium chain fatty acids (MCFAs), on the other hand, are the main components of the medium-chain triglyceride (MCT) ketogenic diet. MCT-based diets are more efficient at generating the ketone bodies that are used as a secondary energy source for neurones and astrocytes. However, ketone levels alone do not closely correlate with improved clinical symptoms. Recent findings suggest an alternative mode of action for the MCFAs, e.g., via improving mitochondrial biogenesis and glutamate receptor inhibition. MCFAs have been linked to the treatment of both aging and neurodegenerative disease via their effects on metabolism. Through action on multiple disease-related pathways, MCFAs are emerging as compounds with notable potential to promote healthy aging and ameliorate neurodegeneration. MCFAs have been shown to stimulate autophagy and restore mitochondrial function, which are found to be disrupted in aging and neurodegeneration. This review aims to provide insight into the metabolic benefits of MCFAs in neurodegenerative disease and healthy aging. We will discuss the use of MCFAs to combat dysregulation of autophagy and mitochondrial function in the context of “normal” aging, Parkinson’s disease, amyotrophic lateral sclerosis and Alzheimer’s disease.